INDONESIAN–ARABIC TRANSLATION OF PHATIC EXPRESSION IN WEBTOON “FLAWLESS” - Washila, Sarah Aufa; Triwinarti, Wiwin (International Review of Humanities Studies, 2019)
This research studies phatic particles translation from Indonesian to Arabic. The discussed translation here includes phatic expression equivalence and translation and form shift. The aim of the study is to analyse the equivalence of phatic expression from Indonesian to Arabic and to look over shift of translation and form so the message from source language is delivered reasonably to target language. The method applied in the study is qualitative descriptive. 105 data were gathered from a webtoon entitled “Flawless” episode 1-10, in Indonesian and Arabic version. To analyse the data, theory of phatic particles in Indonesian from Kridalaksana (1994) is employed. From 105 data, only 24 data were analyzed. The analysis shows that the phatic articles are not completely translated. There are some articles translated accordingly, and some are translated into other forms or absorbed the sound phonetically. There are 7 untranslated particles; 13 translated according their phatic functions; 2 translated into other forms; and 2 absorbed phonetically.